Pengaruh Return On Asset dan Current Ratio Terhadap Dividen Payout Ratio Pada Perusahaan Otomotif Tahun 2018 sampai 2022 - Yosi Afriani; Mike Kusuma Dewi (Universitas 45 Surabaya, 2024)
This research was conducted on the Manufacturing Companies Sub-Sector of Automotive Companies and their components listed on the Indonesian Stock Exchange. This study aims to determine whether the Return on Assets and current Ratio have an influence or not on the partial Dividend Payout Ratio. This research approach uses an associative approach. The population used in this study was 13 companies and the sample that met the criteria (Purposive Sampling) was 8 companies. The data collection technique used in this study awaits documentation techniques and the data source used in this study is a secondary data source published by the company on the official website of the Indonesia Stock Exchange www.idx.co.id. The data analysis techniques used in this study are quantitative, namely multiple linear analysis, hypothesis testing, and determination coefficient tests. Data management using SPSS (Statistical Package For The Social Sciences) version 23 for Windows. The results of this study show that partial Return On Asset does not affect the Dividend Payout Ratio, while the Current Ratio has a positive and significant effect on the Dividend Payout Ratio in Manufacturing Companies, Sub-Sectors of Automotive Companies, and their components listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 period.